Marketing Strategies for Cattle Feed Products in Kerala: an Empirical Study - John M P and Manoj P K (INTERNATIONAL JOURNAL OF SCIENTIFIC RESEARCH, 2013)
Cattle feed industry is a major segment of animal feed industry. This industry is gradually evolving into an organized sector and the feed manufactures are increasingly using modern and sophisticated methods that seeks to incorporate best global practices. This industry has got high potential for growth in India, given the fact that the country is the world’s leading producer of milk and its production is expected to grow at a compounded annual growth rate of 4 per cent. Besides, the concept of branded cattle feed as a packaged commodity is fast gaining popularity in rural India. There can be a positive change in the demand for cattle feed because of factors like (i) shrinkage of open land for cattle grazing, urbanization and resultant shortage of conventionally used cattle feeds, and (ii) introduction of high yield cattle requires specialized feeds. In the above context, this paper looks into the dynamics of cattle feed market in Kerala, emerging purchasing pattern and buyer behavior in respect of cat- tle feed products in the state, and lastly offers a few strategies for effective marketing of cattle feed products.